2016
DOI: 10.1016/j.bpj.2015.11.1470
|View full text |Cite
|
Sign up to set email alerts
|

Zinc Modulates Skeletal Ryanodine Receptor Function Resulting in Altered Sarcoplasmic Reticulum Calcium Release

Abstract: Changes in cardiac ryanodine receptor (RyR2) phosphorylation are thought to be important regulatory and disease related post-translational protein modifications. The extent of RyR2 phosphorylation is mainly determined by the balance of the activities of protein kinases and phosphatases, respectively. Increased protein phosphatase-1 (PP1) activity has been observed in heart failure (HF), but the regulatory role of this enzyme on intracellular Ca 2þ handling remains poorly understood. To determine the physiologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Notably, physiological cytosolic concentrations of Zn 2+ ranging from 100 pM to 1 μM can increase the open probability of the RyR1 channel, while higher concentrations can inhibit ryanodine binding. 24 This dual modulation extends to cardiac muscles, where RyR2 also exhibits zinc concentration dependence, capable of both activating and inhibiting calcium release. Activation likely occurs by binding to the Ca 2+ -activation site, while the inhibitory effect of Zn 2+ may be mediated by the Ca 2+ /Mg 2+ -inhibitory site of RyR1.…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…Notably, physiological cytosolic concentrations of Zn 2+ ranging from 100 pM to 1 μM can increase the open probability of the RyR1 channel, while higher concentrations can inhibit ryanodine binding. 24 This dual modulation extends to cardiac muscles, where RyR2 also exhibits zinc concentration dependence, capable of both activating and inhibiting calcium release. Activation likely occurs by binding to the Ca 2+ -activation site, while the inhibitory effect of Zn 2+ may be mediated by the Ca 2+ /Mg 2+ -inhibitory site of RyR1.…”
Section: Introductionmentioning
confidence: 97%
“…Mutagenesis studies of two ligand residues within the zinc-finger motif have demonstrated their pivotal role in preserving a stable conformation of the RyR1 channel . On the other hand, it has been suggested that Zn 2+ exhibits biphasic modulation in skeletal muscles, similar to calcium, , implying the existence of both activation and inactivation sites. Notably, physiological cytosolic concentrations of Zn 2+ ranging from 100 pM to 1 μM can increase the open probability of the RyR1 channel, while higher concentrations can inhibit ryanodine binding .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation